The Pengaruh Net Interest Margin, Return On Equity Dan Debt To Equity Ratio Terhadap Harga Saham Pada Bank Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2016 -2020 - Wisnu Lesmono; Nunung Nurhasanah; Didit Supriyadi (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The stock market price is a marker dimension of the company's results, namely how far management has managed to manage the company on behalf of shareholders. Evaluation of stock prices can be done by several methods, in certain ways the calculation of stock prices can be done using a form of financial comparison analysis. The purpose of this study is to determine the effect of Net Interest Margin, Return On Equity and Debt To Equity Ratio on stock prices in banks listed on the Indonesia Stock Exchange for the period 2016 - 2020. The type of research conducted is an empirical study of banking companies listed on the IDX. with a quantitative approach. Determination of the sample is done by purposive sampling. In this study, the sample taken was 45 banks with data for the 2016-2020 period. Data collection is done by recording directly on the data that has been published. The data analysis technique used is multiple linear regression where the independent variables are NPM, ROE and DER while the dependent variable is stock price. The results of the study show that there is an influence between NPM, ROE and DER simultaneously on stock prices in banks listed on the IDX for the period 2016 to 2020. Keywords: net interest margin, return on equity, debt to equity ratio, stock price.